Feasibility of clinical detection of cervical dysplasia using angle‐resolved low coherence interferometry measurements of depth‐resolved nuclear morphology. Issue 6 (15th March 2017) - Ho, Derek; Drake, Tyler K.; Smith‐McCune, Karen K.; Darragh, Teresa M.; Hwang, Loris Y.; Wax, Adam
Abstract : This study sought to establish the feasibility of using in situ depth‐resolved nuclear morphology measurements for detection of cervical dysplasia. Forty enrolled patients received routine cervical colposcopy with angle‐resolved low coherence interferometry (a/LCI) measurements of nuclear morphology. a/LCI scans from 63 tissue sites were compared to histopathological analysis of co‐registered biopsy specimens which were classified as benign, low‐grade squamous intraepithelial lesion (LSIL), or high‐grade squamous intraepithelial lesion (HSIL). Results were dichotomized as dysplastic (LSIL/HSIL) versus non‐dysplastic and HSIL versus LSIL/benign to determine both accuracy and potential clinical utility of a/LCI nuclear morphology measurements. Analysis of a/LCI data was conducted using both traditional Mie theory based processing and a new hybrid algorithm that provides improved processing speed to ascertain the feasibility of real‐time measurements. Analysis of depth‐resolved nuclear morphology data revealed a/LCI was able to detect a significant increase in the nuclear diameter at the depth bin containing the basal layer of the epithelium for dysplastic versus non‐dysplastic and HSIL versus LSIL/Benign biopsy sites (both p  < 0.001). Both processing techniques resulted in high sensitivity and specificity (>0.80) in identifying dysplastic biopsies and HSIL. The hybrid algorithm demonstrated a threefold decrease in processing time at a slight cost in classification accuracy. The results demonstrate the feasibility of using a/LCI as an adjunctive clinical tool for detecting cervical dysplasia and guiding the identification of optimal biopsy sites. The faster speed from the hybrid algorithm offers a promising approach for real‐time clinical analysis. Abstract : What's new? Traditional screening programs have drastically decreased cervical cancer rates, but several limitations persist. This is the first clinical feasibility study of angle‐resolved low coherence interferometry (a/LCI) for cervical dysplasia detection. The strength of a/LCI is its depth resolution, enabling detection of increased nuclear diameter at sub‐surface layers of the epithelium and yielding high sensitivity, specificity, and 100% negative predictive value. The results demonstrate the feasibility of using a/LCI as an adjunctive clinical tool for detecting cervical dysplasia and guiding the identification of optimal biopsy sites. The faster speed from the hybrid algorithm offers a promising approach for real‐time clinical analysis.